(untitled) (Community Based Medical Journal, 2013)
This cross sectional descriptive study was done to find out the incidence of accessory spleen in Bangladeshi people to create awareness of the presence of an accessory spleen in a patient prior to splenectomy. During this study one hundred and twenty human cadaver of which eighty-seven male and thirty- three female of different age group were dissected in the morgue of forensic medicine department of Mymesingh Medical College. This was a cross sectional and descriptive study carried out in the department of anatomy of Mymensingh medical college, from July 2007 to June 2008. Accessory spleen was found in 20% cases where 20.68% cases in male and 18.18% in female. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13824 Community Based Medical Journal Vol.1(1) 2012 17-19